Relevansi Nilai Religius Film Ajari Aku Islam terhadap Pendidikan Agama Islam - Muzamil, Muzamil; AR, Fathur Rohman; Hasanah, Nurul (AL-MIKRAJ Jurnal Studi Islam dan Humaniora, 2023)
Islamic Religious Education (PAI) plays an important role in shaping the character and morals of students. In this modern era, mass media, including films, have become a powerful influencer in shaping society's perceptions and values. The film "Ajari Aku Islam" presents a narrative rich in Islamic religious values. However, it is not clear to what extent the religious values ​​conveyed in this film are relevant to PAI material taught in formal education institutions. The aim of this research is to evaluate the relevance of the religious values ​​contained in the film "Ajari Aku Islam" to the PAI material being taught. The analysis will focus on the suitability of Islamic values ​​conveyed in the film with the PAI curriculum. This research uses a qualitative approach with content analysis techniques to identify religious values ​​in the film "Ajari Aku Islam". This literature research uses the documentation method. Namely by collecting data regarding variables in the form of images, sounds and book texts that are related to the religious values ​​in the film Ajari Aku Islam towards Islamic religious education material. The results of this research conclude that the film Ajari Aku Islam is very relevant to the values ​​in Islamic Religious Education lessons, because PAI lessons discuss values ​​such as empathy, tolerance, endeavor, non-discrimination, preaching, obedience and respect for parents, displaying good behavior. which reflects faith, and repentance. With a clearer understanding of the relationship between media and Islamic religious education, steps can be taken to utilize the positive potential of film as an educational tool that supports PAI's goals in shaping the character and morals of students.